Meningkatkan Pemahaman Konsep dan Kolaborasi Siswa: Peran Model Problem Based Learning Terhadap Siswa Kelas V - Rahayu, Putri Nurjati; Aeni, Ani Nur; Sujana, Atep (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – Teacher-centered learning models and a lack of variety limit students' opportunities to be active and think critically, affecting their concept comprehension and collaboration skills. This study aims to investigate the role of the Problem Based Learning (PBL) model on fifth-grade students' understanding of the human respiratory system and organs.Method – This quasi-experimental study used a Non-Equivalent Control Group Design, involving experimental and control classes of fifth-grade students from a public elementary school in Harjamukti District, Cirebon City. Data was collected using testing and non-testing methods. Test instruments used to determine students' concept understanding using pretest and posttest assessments and non-test data is collected using observation.Findings – The results showed that the implementation stages of PBL were carried out very well; both the experimental and control classes showed an increase in concept comprehension, with PBL having a more significant impact. PBL increased concept understanding with an average N-Gain of 57.7% compared to 35.2% in the control class, and increased student collaboration with a percentage of active participation of 84%. Research Implications – The implication in this study is that the PBL model runs very well so that it can significantly improve students' understanding concepts in the material of the human respiratory system and organs. Can also develop students' collaboration skills so that they are more active in class. However, it is limited by its focus on a small sample and specific material. Broader research with diverse samples and materials, or additional variables, is needed for more comprehensive conclusions.